SELF-REGULATION, SELF-EFFICACY, FEAR OF MISSING OUT (FOMO), DAN HASIL BELAJAR IPA: ANALISIS KORELASIONAL DAN KOMPARATIF PADA SISWA SMP - Paramitha, Tristantia Kinanti; Aji, Septiko (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2026)
The success of students' science learning is not only determined by cognitive abilities, but also related to psychological factors and individual characteristics. This study aims to analyze the relationship between self-regulation, self-efficacy, Fear of Missing Out (FoMO), and science learning outcomes in pairs, as well as to examine the differences in these four variables based on gender in junior high school students. This study uses a non-experimental quantitative approach with a correlational-comparative design. The research subjects were 287 eighth-grade students at SMP Negeri 33 Semarang in the 2025/2026 academic year, selected using total sampling technique. Data were collected through a Likert scale questionnaire for the variables of self-regulation, self-efficacy, and FoMO, as well as documentation of final semester exam scores for science learning outcomes. Data analysis was performed using Spearman's correlation and the Mann–Whitney U test. The results showed a strong and significant positive relationship between self-regulation and self-efficacy (r = 0.654; p < 0.05). There was a weak but significant positive relationship between self-regulation and science learning outcomes (r = 0.137; p < 0.05), as well as between self-efficacy and FoMO (r = 0.131; p < 0.05). No significant relationship was found between self-regulation and FoMO, self-efficacy and science learning outcomes, or FoMO and science learning outcomes. The results of the comparative analysis showed significant differences in self-regulation and self-efficacy based on gender, with female students having higher self-regulation and male students having higher self-efficacy. However, there were no significant differences in FoMO and science learning outcomes based on gender. This study shows that the relationship between psychological and academic variables in junior high school students is diverse and influenced by specific contexts. ABSTRAK Keberhasilan belajar IPA siswa tidak hanya ditentukan oleh kemampuan kognitif, tetapi juga berkaitan dengan faktor psikologis dan karakteristik individu. Penelitian ini bertujuan untuk menganalisis hubungan antara self-regulation, self-efficacy, Fear of Missing Out (FoMO), dan hasil belajar IPA secara berpasangan, serta mengkaji perbedaan keempat variabel tersebut berdasarkan jenis kelamin pada siswa SMP. Penelitian ini menggunakan pendekatan kuantitatif non-eksperimen dengan desain korelasional dan komparatif. Subjek penelitian adalah 287 siswa kelas VIII SMP Negeri 33 Semarang tahun ajaran 2025/2026 yang dipilih menggunakan teknik total sampling. Data dikumpulkan melalui kuesioner skala Likert untuk variabel self-regulation, self-efficacy, dan FoMO, serta dokumentasi nilai Ujian Akhir Semester untuk hasil belajar IPA. Analisis data dilakukan menggunakan korelasi Spearman dan uji Mann–Whitney U. Hasil penelitian menunjukkan adanya hubungan positif yang kuat dan signifikan antara self-regulation dan self-efficacy (r = 0,654; p < 0,05). Terdapat hubungan positif yang lemah namun signifikan antara self-regulation dan hasil belajar IPA (r = 0,137; p < 0,05), serta antara self-efficacy dan FoMO (r = 0,131; p < 0,05). Tidak ditemukan hubungan yang signifikan antara self-regulation dan FoMO, self-efficacy dan hasil belajar IPA, maupun FoMO dan hasil belajar IPA. Hasil analisis komparatif menunjukkan adanya perbedaan signifikan self-regulation dan self-efficacy berdasarkan jenis kelamin, dengan siswa perempuan memiliki self-regulation lebih tinggi dan siswa laki-laki memiliki self-efficacy lebih tinggi. Namun, tidak terdapat perbedaan signifikan pada FoMO dan hasil belajar IPA berdasarkan jenis kelamin. Penelitian ini menunjukkan bahwa hubungan antarvariabel psikologis dan akademik pada siswa SMP bersifat beragam dan dipengaruhi oleh konteks tertentu.